Bison movements change with weather: Implications for their continued conservation in the Anthropocene. Issue 12 (8th December 2022) - McMillan, Nicholas A.; Fuhlendorf, Samuel D.; Luttbeg, Barney; Goodman, Laura E.; Davis, Craig A.; Allred, Brady W.; Hamilton, Robert G.
Abstract: Animal movement patterns are affected by complex interactions between biotic and abiotic landscape conditions, and these patterns are being altered by weather variability associated with a changing climate. Some animals, like the American plains bison ( Bison bison L.; hereafter, plains bison), are considered keystone species, thus their response to weather variability may alter ecosystem structure and biodiversity patterns. Many movement studies of plains bison and other ungulates have focused on point‐pattern analyses (e.g., resource‐selection) that have provided information about where these animals move, but information about when or why these animals move is limited. For example, information surrounding the influence of weather on plains bison movement in response to weather is limited but has important implications for their conservation in a changing climate. To explore how movement distance is affected by weather patterns and drought, we utilized 12‐min GPS data from two of the largest plains bison herds in North America to model their response to weather and drought parameters using generalized additive mixed models. Distance moved was best predicted by air temperature, wind speed, and rainfall. However, air temperature best explained the variation in distance moved compared to any other single parameter we measured, predicting a 48% decrease in movement rates above 28°C. Moreover, severe drought (as indicated by 25‐cm depth soil moisture) better predicted movement distance than moderate drought. The strong influence of weather and drought on plains bison movements observed in our study suggest that shifting climate and weather will likely affect plains bison movement patterns, further complicating conservation efforts for this wide‐ranging keystone species. Moreover, changes in plains bison movement patterns may have cascading effects for grassland ecosystem structure, function, and biodiversity. Plains bison and grassland conservation efforts need to be proactive and adaptive when considering the implications of a changing climate on bison movement patterns. Abstract : Animal movement patterns are affected by complex interactions between biotic and abiotic landscape conditions, and these patterns are being altered by weather variability associated with a changing climate. Some animals, like the American plains bison ( Bison bison L.; hereafter, plains bison), are considered keystone species, thus their response to weather variability may alter ecosystem structure and biodiversity patterns. Here, we show that bison movement distances were best predicted by air temperature, wind speed, and rainfall. The strong influence of weather and drought on plains bison movements observed in our study suggest that shifting climate and weather patterns will likely affect plains bison movement patterns, further complicating conservation efforts for this wide‐ranging keystone species.